The Islamic Economic Views on Palm Oil Harvester Wages - Abidin, Zaenal; Safi'i, Imam (Zabags International Journal of Economy, 2023)
The purpose of this study was to describe the wage system for oil palm harvesting workers at PT. Dewa Sawit Sari Persada, Dendang District, and how is the view of Islamic economics related to the wage system for oil palm harvesting workers at PT. Dewa Sawit Sari Persada. This research uses descriptive qualitative methods, and uses field research, namely research conducted in certain environments by conducting direct field studies to obtain concrete data regarding the wage payment system for oil palm harvesting wholesale workers at PT. Dewa Sawit Sari Persada. Data collection techniques through observation, interviews, and documentation. Interviews were conducted with the company, namely estate managers, divisional assistants, harvest foremen, harvest clerks and administrative staff, as well as harvest workers. The results of the research on the wage system for oil palm harvesting workers at PT. Dewa Sawit Sari Persada is not enough when viewed from an Islamic economic perspective because there has been no decision from the company leadership to increase workers' wages, the salary provided is not sufficient for basic needs, no shuttle transportation is provided, no health insurance is provided for workers, there is no guarantee of working days old